Male gametophyte development steps in Pistacia vera L. - ELAHE SADEGHIRAD; AHMAD MAJD; ALIREZA IRANBAKHSH; AMANOLLAH JAVANSHAH (Nusantara Bioscience, 2018)
Sadeghirad E, Majd A, Iranbakhsh A, Javanshah A. 2018. Male gametophyte development steps in Pistacia vera L. Nusantara Bioscience 10: 151-158. Salinity affects the growth and development of plant. It also affects the development steps of male gametophyte in pistachio plant. Pistachio (Pistachio vera) is a member of family Anacardiaceae and order Sapindales. To study the effects of salinity on those steps, an experiment was performed in two locations in Golshan Anar with commensurate circumstances, namely: a control area (A) which was well-irrigated with fresh water, and the other area (B) which was well-irrigated with salty water added with NaCl solution with EC values of 14 dS.m-1. The flowers sampling was done in two Golshan Anar regions on the springtime based on a completely randomized design with three replications. The development steps of male gametophyte in pistachio plant were observed using conventional cell histology techniques and light microscopy observations and were then contrasted with samples subjected to no salinity stress. The results represented that several steps of male gametophyte development are as follows: (1) the anther experiencing normal growth which is tetrasporangiate, (2) cytokinesis taking place simultaneously with meiosis in the microspore mother cell, the tetrahedral tetrads, (3) microspores being delivered after meiosis by microsporogenesis were more or less irregular in shape during the contraction period. Finally, the abnormal shape and structure of the number of cases reviewed in three replicates of pollens can be one of the significant factors influencing the decline in the product.